Transformation in the Nurse-Patient Dyad or the Caregiver-Patient Dyad - Lee, Susan (2018)
Dependent nursing practice is following the doctor’s orders for medications, treatments, diet, activity, tests, etc. We ensure that the medical treatment is given.Shared practice is when the doctor is giving us parameters but leaves us to make judgments, as well. One example is giving medications “as needed” or titrating vasoactive medications in the intensive care unit according to blood pressure.Independent practice is what we do in our own scope of practice. What do we do with and for patients for which we do not need an order?